THE EFFECT OF RELIGIOSITY AND BRAND LOYALTY ON PURCHASE DECISIONS (Case Study at Aurel Hijab Shop in Lhokseumawe City) - Wilda Khaira; Yulius Dharma; Fuadi; Agustinar; Munardi (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of religiosity and brand loyalty on consumer purchasing decisions at the Aurel Hijab Store in Lhokseumawe City. This study uses a quantitative approach with a survey method. The research population is consumers of the Aurel Hijab Store, with a sample size of 100 respondents determined using the Lemeshow formula and convenience sampling techniques. Data collection was carried out through a structured questionnaire with a Likert scale, then analyzed using the Statistical Package for the Social Sciences (SPSS) program through multiple linear regression analysis. The results of the study indicate that partially religiosity (X1) has a positive and significant effect on purchasing decisions (Y), as evidenced by a t-test with a significance value smaller than 0.05. This indicates that the higher the level of consumer religiosity, the stronger their tendency to make decisions to purchase hijab products that are in line with Islamic values. Furthermore, brand loyalty (X2) also has a positive and significant effect on purchasing decisions (Y) based on the t-test results, which indicates that consumer loyalty to the brand encourages repeat purchases and product recommendations. Simultaneously, the F-test results show that religiosity and brand loyalty together have a positive and significant effect on purchasing decisions. The coefficient of determination (R²) value of 76.4% indicates that variations in purchasing decisions can be explained by religiosity and brand loyalty, while the rest is influenced by other variables outside the research model. This finding confirms that consumer purchasing decisions for hijab are not only determined by brand loyalty, but also by the suitability of the product with the religious values held by consumers.